Antibacterial Activity Test of the Combination of Methanol Extract of Arumanis Mango Leaves (Mangifera indica L) and Taro Leaves (Colocasia esculanta L) on Escherichia coli Bacteria Causes of Diarrhea Diseases - Kumalasari, Siska; Fitriyati, Laeli; Rahayu, Titi Pudji; Kiromah, Naelaz Zukhruf Wakhidatul (Jurnal Pijar Mipa, 2024)
Arumanis mango leaves (Mangifera indica L) and taro leaves (Colocasia esculanta L) are plants that have the potential to be antibacterial and can be used as an alternative to treat infectious diseases caused by bacteria. Arumanis mango leaves contain secondary metabolite compounds, including flavonoids, alkaloids, steroids, polyphenols, tannins, and saponins, and taro leaves contain secondary metabolite compounds in the form of saponins, tannins, flavonoids, formic acid, glucosides, citric acid, and several minerals. Secondary metabolite compounds that have potential as antibacterials are flavonoids and tannins. This study aims to determine the antibacterial activity of a combination of methanol extracts of arumanis mango leaves (Mangifera indica L) and taro leaves (Colocasia esculanta L) against Escherichia coli bacteria. The research was carried out starting from the plant determination and preparation of simplisia, extraction, phytochemical screening of extracts and KLT tests, and antibacterial testing using the disc paper method. The concentration series of extract combinations used are 6.25%, 12.5%, and 25%. The antibacterial test results of the combination of arumanis mango leaf extract (Mangifera indica L) and taro leaf (Colocasia esculanta L), which showed the highest inhibition zone diameter was at a concentration of 6.25% (1:1), a concentration of 12.5% (1:2). At a concentration of 25% (2:1). From the results of this study, a single extract of arumanis mango leaves and taro leaves with a concentration of 6.25%; 12.5%; 25% and a combination of extracts in a ratio of 1:1. 1:2, 2:1, which has potential antibacterial activity against Escherichia coli bacteria, so that further research can be carried out by utilizing a combination of arumanis mango leaf extracts and taro leaves and as a source of information and insight into the combination of arumanis mango leaves and taro leaves that have antibacterial properties.